The effect of Baduanjin exercise on health-related physical fitness of college students: A randomized controlled trial - Ye, Yu; Zhao, Fang; Sun, Shanshan; Xiong, Jian; Zheng, Guohua (Frontiers in Public Health, 2022)
Background The continuous decline in the physical fitness of college students has become a serious social problem worldwide. Therefore, it is necessary to explore the effective method improving college students' physique. Previous studies have shown that Baduanjin exercise is beneficial in improving sleeping quality, mental health, body flexibility, and body physique. However, the evidence is unclear whether Baduanjin exercise can be recommended as an effective exercise to promote health-related physical fitness of college students. Methods A total of 130 college students were recruited and randomly allocated to either the Baduanjin training or the control group at a ratio of 1:1. The students in the Baduanjin training group received a 12-week supervised Baduanjin exercise training intervention with a frequency of 1 h each day and 4 days per week, while those in the control group did not receive any specific exercise intervention and were informed to maintain their original lifestyle for 12 weeks. The outcomes of health-related physical fitness involving measurements of body flexibility, muscular strength, cardiopulmonary fitness, and body endurance were measured at baseline and after the 12-week intervention period. Mixed linear model was used to analyze the effect of the Baduanjin exercise intervention. Results Mixed linear model analyses showed that the Baduanjin training group had a significant increase in the composite scores of health-related physical fitness compared to the control group from baseline to 12-week post-intervention with a medium effect size (d = 0.68, P = 0.006). Moreover, there were significant improvements in vital capacity, physical flexibility, 800/1,000 m endurance running, and body composition (measured by body mass index (BMI), fat mass and body fat ratio) at end of 12-week intervention in the Baduanjin training group. No adverse events were observed in this trial. Conclusion Regular Baduanjin training may be an effective, safe exercise form to promote the health-related physical fitness of young adults. Trial registration Chinese Clinical Trial Registry, ChiCTR-IOR-17013011. http://www.chictr.ogr.cn.